Relationships between the characteristics weaning-to-estrus interval, estrus duration and moment of ovulation by ultrasonography in sows - Viana, Carlos Henrique Cabral; Silveira, Paulo Roberto Souza da; Moretti, Anibal SantAnna; Rodrigues, Paulo Henrique Mazza (Brazilian Journal of Veterinary Research and Animal Science, 1999)
Relationships between weaning-to-estrus interval (WEI), duration of estrus (DE) and moment of ovulation (MO) were studied. A total of 236 sows were observed to record the data of WEI and DE, which were tested by back pressure 4 times a day, in the presence of a boar. The ovulation was diagnosed in 77 sows, by transcutaneous ultrasonography, 3 times a day at 8-hour interval. There was negative correlation between WEI and DE (r=-0.4657; p=0.0001) and between WEI and MO (r=-0.3955; p=0.0004), however, there was no correlation between DE and MO (r=0.2201; p=0.0578). The percentage of females that ovulated between 0 to 24, 24 to 48, 48 to 72 and over 72 hours after the onset of estrus was, respectively, 0%, 58.4%, 37.5% and 4.2% to WEI of 3 days, 3.2%, 67.7%, 29.2% and 0% to WEI of 4 days, 0%, 91.6%, 8.3% e 0% to WEI of 5 days and 10%, 90%, 0% and 0% to WEI of 6 and 7 days. In these conditions, the WEI was not a good reference to be utilized as a predictor of ideal moment of insemination. However, the information about the characteristics WEI, DE and MO within each herd help to point the mistakes and to develop AI programs.